The Effectiveness of Al-Quran Learning with Google Meet Media in Improving the Quality of Students' Al-Quran Reading in Junior High Schools: Efektivitas Pembelajaran Al-Quran dengan Media Google Meet dalam Meningkatkan Kualitas Bacaan Al-Quran Siswa di Sekolah Menengah Pertama - Nashihuddin, Nashihuddin; Astutik, Anita Puji (Universitas Muhammadiyah Sidoarjo, 2022)
This research was motivated by the beginning of the Covid 19 pandemic, which required educational institutions to organize online learning processes. Muhammadiyah 3 Waru Middle School Sidoarjo initially held face-to-face Al-Quran learning in class, but since the implementation of online learning, Muhammadiyah 3 Waru Middle School uses Zoom as an online learning platform. Over time, there were many shortcomings in the Zoom platform such as pay, limited time and number of users, so SMP Muhammadiyah 3 Waru switched to the Google Meet platform. This study aims to determine the effectiveness of learning the Koran by using Google Meet online media in improving the quality of reading the Koran for students at SMP Muhammadiyah 3 Waru, Sidoarjo. This study uses a Quantitative Experimental research method. The data taken by the researcher is in the form of numbers that will be tested through the SPSS program. The data collection technique used in this research is to collect data in the form of student learning outcomes before using Google Meet media or when face to face and after using Google Meet Media. The data analysis uses the t test test in the SPSS program to determine whether there is a significant change in learning the Koran using Google Meet media. The results of this study indicate that learning the Koran with Google Meet media is not effective. It was found that there was a decrease in student scores during the pretest and posttest. From the decrease in the results of this score, it has shown a benchmark for whether or not Google Meet media is effective in learning the Koran